Effect of Ethanol on Critical Micelle Concentration of Sodium Dodecylsulphate in Mixed Solvent Media at 308.15K by Conductometric Measurement - Yadav, Chandradip Kumar; Yadav, Brahamdeo (Orchid Academia Siraha, 2022)
The conductivity measurement of sodium dodecyl sulphate (SDS)in mixed solvent media was investigated. The results indicated that sharp increase with the increase in concentration and temperature of sodium dodecyl sulphate the critical micelle concentration (CMC) decreased with the amount of ethanol increase which can be explained based on the nature of solvent mixed media and inter ionic attraction of ions. The graph of conductance versus concentration is used to determine the critical micelle concentration (CMC).